Computational topology in image context : 6th International Workshop, CTIC 2016, Marseille, France, June 15-17, 2016, Proceedings /: 6th International Workshop, CTIC 2016, Marseille, France, June 15-17, 2016, Proceedings. (2016) - Unknown
No abstract available